In situ observation of sexual reproduction of Holothuria tubulosa Gmelin 1788 (Echinodermata: Holothuroidea) in the Azores (NE Atlantic) - Andrade, Áthila A. (2008)
[...]. In the Azores, H. tubulosa spawning occurs in the summer months (so far observed in July and August) during the afternoon, which may follow the annual pattern, during warm sea temperatures (22–26°C) and being synchronous in both sexes, as stated by Despalotovic et al. (2004) in the Adriatic Sea. [...]